Analisa Kualitas Layanan Web Pendaftaran Online Pada MI Satria Menggunakan Metode Servqual - Nurul Fitri Amalia; Eva Zuraidah (STMIK Budi Darma, 2022)
The problem raised in this study is whether the use of online new student admission information systems at MI SATRIA DKI Jakarta has an effect on user satisfaction. PPDB Online is still poorly understood by prospective students because of the complicated registration system process and the lack of knowledge in the IT field for prospective students who want to register. The problems that arise because of concerns about the difficulty of registering are aimed at knowing and analyzing the effect of service quality consisting of reliability, responsiveness, assurance, empathy, and tangible variables on user satisfaction. From the calculation results, the GAP value is obtained based on the ranking, namely, responsiveness, ranking 1, GAP value -1.95, reliability ranking 2 with GAP value -1.92, assurance ranking 3 with GAP value -1.86, ranking 4 empathy with GAP value -1, 83, ranked 5 tangible with a GAP value of -1.51. The method is by analyzing the gap between the expected service variable and the perceived service. Importance Performance Analysis and 5 dimensions of service quality consist of tangibles, reliability, responsiveness, assurance, and empathy. And in the implementation problem in quadrant 1 the quality of service is still said to be low and must be improved. The effect of user satisfaction when viewed from the IPA diagram, there are the most attributes in quadrant 2, namely the quality of website services that have been fulfilled and must be maintained, but when viewed from user satisfaction from the five dimensions of service quality there is a gap between expectations and the reality of the services received with a value of less than 1, it can be said that it is still not optimal in user satisfaction.